Cardiovascular benefits related to the use of SGLT-2 protein inhibitor drugs (Research, Society and Development, 2024)
Sodium and glucose co-transporters (SGLT) are proteins that act by transferring sodium into cells, particularly with glucose, so that subtype 2 (SGLT-2) can reabsorb filtered glucose. In 2019, the American Diabetes Association recommended the use of SLGT-2 inhibitor drugs in patients with atherosclerotic cardiovascular disease at risk of heart failure. These medications alleviate heart injuries, thereby reducing deaths, nonfatal myocardial infarction, stroke, and hospitalizations for heart failure. This study will seek to discuss the cardiovascular benefits obtained from the use of these medications. This is a systematic review of the literature based on the guiding question: “What cardiovascular benefits can be obtained with the use of drugs that inhibit the SGLT-2 protein?” with a bibliographic survey carried out in the PUBMED database. The Controlled Health Sciences Descriptors (DeCS) used were: Sglt2; Cardiac insufficiency. Thus, 40 clinical trials published between 2017 and 2023 were selected according to the objective of the research and which met the inclusion criteria: articles published in English, Portuguese or Spanish, whose titles and abstracts were shown to be in accordance with the purpose. of the literature review, indexed in the aforementioned database. Repeated articles, theses, dissertations and analysis summaries were excluded. An analysis highlighted the benefits of SGLT-2 inhibitor drugs: improvements in energy pathways, antifibrotic effects and improved quality of life. In the stages, a reduction in hospitalizations, mortality and an increase in life expectancy were observed.